A genome-wide association study uncovers a critical role of the RsPAP2 gene in red-skinned Raphanus sativus L. (24th September 2020) - Fan, Lianxue; Wang, Yan; Xu, Liang; Tang, Mingjia; Zhang, Xiaoli; Ying, Jiali; Li, Cui; Dong, Junhui; Liu, Liwang
Abstract: Radish ( Raphanus sativus L.) taproot contains high concentrations of flavonoids, including anthocyanins (ATCs), in red-skinned genotypes. However, little information on the genetic regulation of ATC biosynthesis in radish is available. A genome-wide association study of radish red skin color was conducted using whole-genome sequencing data derived from 179 radish genotypes. The R2R3-MYB transcription factor production of anthocyanin pigment 2 ( PAP2 ) gene was found in the region associated with a leading SNP located on chromosome 2. The amino acid sequence encoded by the RsPAP2 gene was different from those of the other published RsMYB genes responsible for the red skin color of radish. The overexpression of the RsPAP2 gene resulted in ATC accumulation in Arabidopsis and radish, which was accompanied by the upregulation of several ATC-related structural genes. RsPAP2 was found to bind the RsUFGT and RsTT8 promoters, as shown by a dual-luciferase reporter system and a yeast one-hybrid assay. The promoter activities of the RsANS, RsCHI, RsPAL, and RsUFGT genes could be strongly activated by coinfiltration with RsPAP2 and RsTT8 . These findings showed the effectiveness of GWAS in identifying candidate genes in radish and demonstrated that RsPAP2 could (either directly or together with its cofactor RsTT8) regulate the transcript levels of ATC-related genes to promote ATC biosynthesis, facilitating the genetic enhancement of ATC contents and other related traits in radish.